SISTEM INFORMASI PERPARKIRAN DI HOTEL GRAND ANUGRAH - Machudor Yusman; Anie Rose Irawati; Riky Putra Jumara (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2014)
Nowadays, companies both large and small have flocked to use the help of science and technology in support ofthe company's operational processes. In this study will be made of software for Service Information System Centreso it can easily run the application in a parking lot and can facilitate corporate leaders in monitoring the parkingreports results every time. The software is designed using Adobe Flash, and created with Visual Basicprogramming, Seagate cristal Report with the Microsoft Office Access database. Their software for the parkingsystem is expected to be better in terms of security, speed, and order at the time of parking in the parking area.Keywords: Information Systems, Visual Basic, Adobe Flash.